Egressos da licenciatura em artes visuais da Universidade Federal da Paraíba e sua inserção profissional - Dias, Martha Pollyanna dos Santos (2013)
This study aims at knowing what is expected from students who graduated in Visual Arts at UFPB and how they are finding a position in the job market. This is a desk research, which uses as reference the National Guidelines for Undergraduate Courses, the National Exam for the Evaluation of Visual Arts Undergraduate Students, the Pedagogical Project of the Visual Arts Undergraduate Course, its resolution and the resolution that created the Undergraduate Course in Artistic Education, as well as my personal experience as a Visual Arts major and applicant for a position in the job market. It is a case study research, which aims at interviewing students who graduated in Visual Arts in 2007 and 2008. This is still an ongoing research.